Golf shaft fitting calibration system - Jaknowan, J.; Mitatha, S.; Vongchumyen, C.; Yupapin, P. P. (Procedia Engineering, 2012)
The calibration system was developed for golf shaft fitting to the club or blade. The system provided the best line and angle of golf shaft to fit into the club slot. This yielded the best controlling for the impact point between the club and the golf ball, including obtained the minimal swaying of golf shaft after the club hit to the ball. The proposed system was consisted of two components: the hardest line tuning and the best line calibration tool. The hardest line tuning was applied to search for the line that indicated the most strongest of the shaft, which contributed the minimal bend within the given certain forced pressure. The best line calibration tool was employed to determine the best angle for fitting the shaft to the golf club which reflected the minimal swaying while hitting to the ball. In this manner, the golfers could control the desired range and direction of the ball.